PENGARUH FRAKSI VOLUME SERAT GELASTERHADAP KETAHANAN BAKAR KOMPOSITDENGAN MATRIKS RIPOXY R-802 EX - Hanif, Wakhid Nurrohman (Jurnal Nosel, 2014)
The objectives of this research are to investigate: (1) the effect of volume fraction variations on the fire resistance of the glass fiber composite with the matrix of Ripoxy R-802 EX; and (2) glass fiber volume fraction with the highest fire resistance ofthe glass fiber composite with the matrix of Ripoxy R-802 EX. This research used the experimental research method. It was conducted at the Engineering Material Laboratory, the Department of Mechanical Engineering, the Faculty of Engineering, SebelasMaret University, Surakarta. The instrument used to investigate the fire resistance of the composites was fire resistance testing device of ASTM D-635. The specimenof the research was glass fiber composite with the matrix of Ripoxy R-802 EX with the glass fiber fraction compositions of 15%, 25%, 35%, and 45% respectively. The fire resistance testing of the composite was done according to the standard of ASTM D-635. The indicators of the fire resistance were determined based on the time of burning (TOB) and the rate of burning (ROB). The data of the research were analyzed by using the comparative descriptive technique of analysis.The results of the research are as follows. 1) The more the content of the glass fiber content was, the time of burning was increasing but the rate of burning was decreasing. This indicates that the larger the glass fiber content is, the fire resistance of the composites is increasing, that is, increasing the value of the TOB but decreasing that of the ROB. 2) In accordance with the standard of ASTM D-635 for the fire resistance testing with the method of the horizontal burning test, the use of the glass fiber with the content of 45% in the composite made this composite possess the highest burning resistance.